2022
DOI: 10.1186/s12885-021-09157-w
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in women with breast cancer: a review of measures

Abstract: Background To identify and describe the breast cancer–specific health-related quality of life (HRQoL) instruments with evidence of validation in the breast cancer population for potential use in patients treated for breast cancer (excluding surgery). Methods We conducted a systematic literature review using PubMed, Embase, and PsycINFO databases to identify articles that contain psychometric properties of HRQoL instruments used in patients with bre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…The Quality of Life (QoL) is an individual's perspective on life based on his or her current circumstances (17,18). Aside from this subjective aspect, QoL instruments are highly valid, reliable, and responsive for measuring important clinical changes and comparing different types and levels of diseases, treatments, or interventions in different situations at a specific time (19,20). A previous study indicated the evaluating adjuvant therapy treatments in 530 cancer patients treated with tamoxifen experience side effects in their emotional, functional, and sexual functions that are manifested in, among others, sleep disturbances, hot flushes, vaginal dryness, and depression (21).…”
mentioning
confidence: 99%
“…The Quality of Life (QoL) is an individual's perspective on life based on his or her current circumstances (17,18). Aside from this subjective aspect, QoL instruments are highly valid, reliable, and responsive for measuring important clinical changes and comparing different types and levels of diseases, treatments, or interventions in different situations at a specific time (19,20). A previous study indicated the evaluating adjuvant therapy treatments in 530 cancer patients treated with tamoxifen experience side effects in their emotional, functional, and sexual functions that are manifested in, among others, sleep disturbances, hot flushes, vaginal dryness, and depression (21).…”
mentioning
confidence: 99%
“…[28][29][30][31] Several systematic reviews have been conducted with the goal of identifying which major PROMs questionnaires have been developed specifically for patients with breast cancer facing different stages of disease and treatments. [32][33][34] An interesting example is the work realized by van Egdom et al 32 This review investigated the implementation methods, impact facilitators, and barriers of PROM collection in breast cancer clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…QOL was assessed using the German version of the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30; version 3.0). This is a widely used questionnaire that has been validated in different patient groups and many languages [ 15 , 35 ]. The EORTC QLQ-C30 comprises 30 items divided among five functional scales (physical, role, cognitive, emotional, and social functioning), nine symptom scales/items (fatigue, nausea/vomiting, pain, dyspnoea, insomnia, appetite loss, constipation, diarrhoea, financial difficulties), and a global health/QOL scale.…”
Section: Methodsmentioning
confidence: 99%